A escrita como desaparecimento nos romances de Enrique Vila-Matas - Toso, Francielli Noya (2016)
The novel Doctor Pasavento, written by Enrique Vila-Matas, appears in the contemporary scenery as a narrative that intents to regain a prominent position in the literature. Its narrator, a veteran writer searching for the beginning of the writing, when it paradoxically disappears, it is circulating around the world, registering its experiences in a diary. He resorts to the literary tradition and builds himself as a complex character made of paper that sometimes destroys its fictional condition and sometimes embodies the destiny of the literature, that, for him, it is to disappear. Considering the narrator's actions, this dissertation proposes an analysis of the self reflective practice in the literary prose of the writer Enrique Vila-Matas, with special attention to the novel Doctor Pasavento (2009). The theoretical starting point in this proposition is in the context of the discussion coined by some contemporary scholars as "the return of the author", which questions many self referential procedures in some recent narratives, and at the same time rethinking the premise of the death of the author. Taking into consideration the contemporary studies turned to the self writing in convergence with the thoughts of Maurice Blanchot, Roland Barthes, Michel Foucault, and others, this paper verifies how Vila-Matas' writing, through his meta fictional resources, discusses with those thinkers and other writings of the philosophical and literary tradition. This research takes into consideration how autobiographical strategies were taken and relocated in the said novel, considering a time where, before the unstoppable growth of the media activity, it has become even more problematic defining categorical boundaries between reality and fiction. The points around the effect of the activity towards the media on the literary system is part of the reflection of the vila-matasians narrators, contributing to one of the author's obsession: the disappearance. This theme is discussed here from the visibility logic in the contemporary scenery, which offers many resources to expose the subject. That way, the central theme of Vila-Matas' novel gets a paradoxical approach, when considering the appearing/disappearing game in the literary writing in relation with the forces of exposition and fading offered by the devices of the media. The novel Montano's Malady (2005), that joins along Doctor Pasavento (2009) in a sequence known as "tetralogía del autor", also has an important role in this dissertation, once that it invests in the staging of the subjectivity that continues in Doctor Pasavento and, because of that, it contributes to the identification of the consequences of the self reflexive practice in Vila-Matas' prose.